Learning of Akidah Akhlak Using Smart Wheel Media at MTS Surya Buana Malang City - Fatih Ihsan; Romelah Romelah (Universitas Muhammadiyah Enrekang, 2022)
This study aims to describe the learning process of Akidah Akhlak using Smart Wheel as the media, and the implementation of Smart Wheel media. This Research carried out by using a qualitative approach, through cases study type of research. Subject of the research are Akidah Akhlak teacher and 8th graders students, the research was taken in Madrasah Tsanawiyah Surya Buana in Malang City. The data collection techniques are observation, interview, and documentation, as for the results: First, the teacher makes or prepares list of questions. Second, students spin the wheel until stops. Third, students see the questions or commands in each column, then students answer the question based on where the arrow’s stop, and the last step is the teacher gives grade to students from 0-100 based on the students answer. This smart wheel media makes students interested in Aqidah Akhlak class and encourage a creative sense in KD 3.2 which is about commendable morality for themselves, through the smart wheel media in learning Akidah Akhlak. Students are very enthusiastic and the teacher easily conveys the material by using the smart wheel media